Incorporation of N in the TiO2 Lattice Versus Oxidation of TiN: Influence of the Deposition Method on the Energy Gap of N-Doped TiO2 Deposited by Reactive Magnetron Sputtering - Duarte,Diego Alexandre (2017)
N-doped TiO2 can be deposited by reactive magnetron sputtering by two methods: incorporation of nitrogen particles in the TiO2 lattice or incorporation of oxygen particles in the TiN lattice (oxidation). This paper investigates both procedures by experimental and numerical methods in order to establish the best way for incorporation of substitutional nitrogen in the TiO2 lattice. Films were deposited with different oxygen and nitrogen flow rates for fixed values of argon flow rate, working pressure, DC power, film thickness and target-to-substrate distance. After deposition, samples were characterized by optical spectrophotometry to calculate the energy gaps. The mechanism for incorporation of substitutional nitrogen was investigated by a numerical model based on Berg model, where data were faced to experimental data in order to validate the growing mechanism. Results indicate that the deposition with oxygen flow rates lower than that set for nitrogen decreases the energy gap due to the incorporation of substitutional nitrogen in the film lattice and depositions with high oxygen flow rates decrease the amount of nitrogen in the film lattice due to the fast oxidation of the nitride layers caused by the high sticking coefficient of the oxygen particles.